Shared Genetics Between Schizophrenia and Cardiometabolic Diseases: A Large-Scale Genome-Wide Cross-Trait Analysis - Salameen, Tasnim Ahmad Mohammad (My University, 2026)
Abstract Schizophrenia (SCZ) is a chronic mental disease, with a worldwide prevalence of about 1%. While epidemiological studies demonstrate the comorbidity of SCZ with cardiometabolic traits, the genetic basis, causality of association, and pathophysiology of this comorbidity are poorly understood. Thus, this study intended to explore shared genetics between SCZ and cardiometabolic traits. Utilizing genome-wide association study (GWAS) summary data with sample sizes ranging from 50,364 to 898,130 of European ancestry, linkage-disequilibrium logistic regression (LDSC) was used to assess the heritability and the genetic correlation of SCZ with cardiometabolic traits, and a large-scale genome-wide cross-trait meta-analysis was conducted to investigate the genetic overlap between SCZ and cardiometabolic disorders. Multi-trait fine mapping and colocalization analyses were conducted to identify putative causative and shared causal variants, respectively. MAGMA gene-level analysis was integrated to identify significantly associated genes. Enrichment analyses were used to identify differential tissue expression and major shared pathways. Finally, the generalized summary statistic-based Mendelian randomization (GSMR) was applied to assess causation. LDSC revealed a significant negative genetic correlation of SCZ with type 2 diabetes, cardiometabolic multimorbidity, obesity class 1, and obesity class 2. Cross-trait meta-analysis identified 124 independent SNPs, of which 7 SNPs are novel. Multi-trait fine mapping identified 90 putative causative SNPs, of which 15 SNPs are novel, and colocalization analysis revealed 9 shared causative SNPs between SCZ and T2D. MAGMA gene-level analysis revealed 94 significant shared genes. Enrichment analyses pinpointed a complex genetic interplay, with possible inflammatory, metabolic, and oxidative stress mechanisms. GSMR analysis suggested a possible weak causal link between SCZ and cardiometabolic traits in this study. This large-scale genome-wide cross-trait analysis identified shared genetics, suggesting common biological mechanisms underlying their comorbidity. ملخص الدراسة الفصام هو مرض عقلي مزمن، ويبلغ معدل انتشاره حوالي 1% عالمياً. تُشير الدراسات الوبائية إلى الاعتلال المشترك بين الفصام والاضطرابات القلبية والأيضة، مع ذلك، فإن الأسس الجينيّة والعلاقة السببية والفسيولوجيا المَرَضيّة لهذا الاعتلال المشترك لا تزال غير مفهومة بشكل كامل. لذا فإن هذه الدراسة تهدف إلى استقصاء العوامل الجينية المشتركة بين الفصام والسمات القلبية-الأيضية. باستخدام بيانات احصائية لأفراد من أصول أوروبية من دراسات الترابط على مستوى الجينوم (GWAS) وتتراوح أحجام العينات فيها من 50,364 و898,130، حيث استُخدم تحليل الانحدار اللوجستي لتحليل الارتباط غير المتكافئ (LDSC) لتقييم وراثة هذه الأمراض وكذلك التداخل الجيني بين الفصام والاضرابات المتعلقة بالقلب والأيض، كما أُجري تحليل التباين الشمولي عبر السمات (cross-trait meta-analysis) واسع النطاق على مستوى الجينوم لدراسة التداخل الجيني بين الفصام واضطرابات القلب والأيض. كما أُجري تحليل التحديد الدقيق مُتعدد السمات (multi-trait fine mapping)وتحليل التَمَوضُع المُشترك (Colocalization) لتحديد المتغيرات الجينيّة السببية المحتملة والمشتركة. كما تم استخدام MAGMA لتحديد الجينات المرتبطة وذات دلالة إحصائية. استُخدمت تحليلات الإثراء (enrichment analysis) لتحديد التعبير الجيني التفاضلي في الأنسجة وكذلك المسارات البيولوجيّة المشتركة. أخيراً، تم تطبيق أسلوب العشوائية المندليّة (GSMR)لتقييم السببيّة. كشف تحليل LDSC عن وجود ارتباط جيني سلبي ذو دلالة إحصائية بين الفصام وداء السكري من النوع الثاني، وتعدد الأمراض القلبية الأيضية، والسمنة من الدرجة الأولى، والسمنة من الدرجة الثانية. كما نتج عن تحليل التباين الشمولي عبر السمات 124 متغيرًا جينيًا مستقلًا، منها 7 متغيرات مُحدَثة. كما كشف تحليل التحديد الدقيق مُتعدد السمات عن 90 متغيرًا جينيًا يُحتمل أن تكون مسببة، منها 15 متغيرًا مُحدَثاً وكشف تحليل التَمَوضُع المُشترك عن 11 متغيراً جينياً مسبباً للفصام ومرض السكري من النوع الأول. وأظهر تحليل MAGMA على مستوى الجينات 94 جينًا مشتركًا ذا دلالة إحصائية. وأشارت تحليلات الإثراء إلى تفاعل جيني معقد، مع آليات محتملة تشمل الالتهاب، الأيض، والإجهاد التأكسدي. وأشار تحليل العشوائية المدليّة إلى وجود مسؤولية جينية ضعيفة بين الفصام والأمراض القلبية الأيضية في هذه الدراسة. كشف هذا التحليل الشامل للجينوم عن سمات جينية مشتركة، مما يُشير إلى وجود آليات بيولوجية مشتركة وراء التزامن المرضي.
Number of pages 100
Keywords: Genome; Biotechnology